2020
DOI: 10.1186/s12931-020-01497-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal sleep, physical activity and screen time during pregnancy on the risk of childhood respiratory allergies: a sex-specific study

Abstract: Background: Early life exposure in the uterus had a long-term effect on children's health. As the prevalence of allergies is increasing with a remarkable sex difference, very few studies have traced back to their early origins. We sought to investigate if maternal behavioral exposure, herein sleep, physical activity, and screen time during pregnancy is associated with childhood respiratory allergies. The sex difference would be examined. Methods: Six thousand two hundred thirty-six mother-child pairs from Shan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Consistent with earlier studies [ 12 , 14 , 23 , 27 , 40 , 42 ], this study also found that maternal asthma during pregnancy, smoking during pregnancy, and pre-pregnancy obesity were significantly associated with increased risks of wheezing and asthma among Australian children. Childhood eczema was associated only with maternal asthma during pregnancy and not with pre-pregnancy obesity, smoking during pregnancy, or antibiotic/antidepressant medication use during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with earlier studies [ 12 , 14 , 23 , 27 , 40 , 42 ], this study also found that maternal asthma during pregnancy, smoking during pregnancy, and pre-pregnancy obesity were significantly associated with increased risks of wheezing and asthma among Australian children. Childhood eczema was associated only with maternal asthma during pregnancy and not with pre-pregnancy obesity, smoking during pregnancy, or antibiotic/antidepressant medication use during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Based on existing literature [ 3 , 13 , 14 , 32 ], this study considered the following confounding variables. Socio-demographic covariates included were (i) age of the mother (<=18, 19–34, > = 35 years), (ii) gender of the child (male or female), (iii) whether English is spoken at home (yes or no), (iv) whether mother is married with a partner, with a de facto partner, or single, (vi) indigenous status (yes or no), (vii) education of the mother (year 12 or less, professional qualification, graduate diploma, or postgraduate), (viii) family income (five quantiles), and (ix) remoteness of the family residence (highly accessible, accessible/moderately accessible, or remote/very remote).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations